INCREASING QUALITY OF VOICE CALL (QOVC) USING LIGHTWEIGHT DEEP LEARNING ALGORITHM (LWDLA) IN GSM COMMUNICATION (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Global system for mobile communication (GSM) is an internationally recognized standard for digital mobile communication. However, the quality of voice calls remains a critical factor in the development of GSM. This paper proposed a deep learning algorithm to ensure the voice call quality of the cellular communication networks. The suggested model continuously analyzes the voice data packets to guarantee that the correct message is conveyed from the sender to the recipient. The station receives the phone's special identification code. The station and phone keep a continual radio connection and occasionally exchange packets. Matlab was used to simulate a variety of performance criteria, including quality of service measurements. The simulation analysis indicates that the proposed method has an average QoS rate of 97.35 percent, more significant than the present method.